The Philippines and the law of the sea a collection or articles, statements, and speeches - Tolentino, Arturo M. (Makati, M. M. Development Academy of the Philippine Press, 1982)
Distribution statement from label mounted on t.p."First published in Philosophical transactions of the Royal Society of London: part A in series A, volume 291 ... part B in series B, volume 284."Includes bibliographies and indexes.
Keywords: Maritime law; Law of the sea